Effects of the ethanol extract of black mulberry (Morus nigra L.) fruit on experimental atherosclerosis in rats. (22nd March 2017) - Jiang, Yan; Dai, Min; Nie, Wen-Jing; Yang, Xiao-Rong; Zeng, Xian-Chun
Abstract: Ethnopharmacological relevance: Atherosclerosis (AS) is the major pathogenic component of coronary artery and cardiovascular disease. Studies have increasingly focused on natural medicines that have lipid-lowering, anti-inflammatory, and endothelial–protection activities. Black mulberry fruits are traditionally used in Uyghur folk medicine for the prevention and treatment of cardiovascular diseases in southern Xinjiang region of China. However, its underlying mechanisms remain unknown. Thus, our objective was to explore the effects and underlying mechanisms of ethanol extract of black mulberry (EEBM) in experimental atherosclerotic rats. Materials and methods: The black mulberry fruit was extracted with acid ethanol and chromatographed on an AB-8 macroporous resin to obtain EEBM. Atherosclerotic rats were divided into five groups: normal, model, model plus simvastatin (5 mg/kg d·body weight), and model plus low-dose and high-dose EEBM groups (105 and 210 mg/kg d·body weight, respectively). Serum lipid profiles were measured by an automatic biochemistry analyser. The activities of anti-oxidative enzymes were determined using the chemical colorimetric method. Pathological changes in liver and arteries were examined by hematoxylin and eosin (H&E), and the intima-media thickness was measured. Results: The high-dose EEBM group showed significantly reduced total cholesterol, triglyceride, and low-density lipoprotein-cholesterol levels, as well as atherogenic index. Furthermore, treatment with high-dose EEBM markedly decreased malondialdehyde content and enhanced anti-oxidative enzyme activities. Histopathological examination showed that EEBM attenuated hepatic steatosis and reduced intima-media thickness and arterial atherosclerotic lesions in atherosclerotic rats. These results suggest that EEBM suppressed atherosclerosis development in atherosclerotic rats by regulating lipid metabolism abnormalities, enhancing anti-oxidative activities, and reducing atherosclerotic lesions, which could be attributed to anthocyanins (23.75%), or the cooperative action of anthocyanins, polyphenols (2.95%), and flavonoids (0.94%). Graphical abstract: